Pengaruh kualitas pelayanan terhadap kepuasan pasien: Studi pada rumah sakit swasta di Kota Malang - Wahyuni, Wahyuni; Asna, Asna; Hidayat, Candra Wahyu (MBR (Management and Business Review), 2024)
This study aims to analyze the impact of service quality on patient satisfaction in private hospitals in Malang City. The concept of service quality is evaluated through five variables: physical evidence, reliability, responsiveness, assurance, and empathy. This study used quantitative methods through surveys to collect data from 150 inpatients. The results of the simultaneous analysis show that the dimensions of physical evidence, reliability, responsiveness, assurance and empathy have an influence on patient satisfaction. Meanwhile, partially the empathy dimension has no effect on patient satisfaction, while the dimensions of physical evidence, reliability, responsiveness, and guarantee each have an influence on patient satisfaction. These findings highlight the importance of improving service quality in an effort to increase patient satisfaction. Thus, research is expected to make a positive contribution to the development of hospital management strategies that are more effective and adaptive to patient needs.